Athletic population with spondylolysis: review of outcomes following surgical repair or conservative management - Panteliadis, Pavlos; Nagra, Navraj S.; Edwards, Kimberley L.; Behrbalk, Eyal; Boszczyk, Bronek (SAGE, 2016)
Objective